Pt Rti Production Division Manpower Planning Based On Workload Analysis Using Work Sampling Method - Alfian Kusuma Aji; Atya Nur Aisha; Yussi Perdana Saputera (eProceedings of Engineering, 2021)
Human resources have a role to support the realization of the company's strategic plan and increase company productivity. In the last three years PT RTI can’t fulfill the demand target on time and also due to the lack of manpower, causing the workload in the production division to increase. Workload analysis and manpower planning will be done by using work sampling method. Result of calculation is a standard time that can be used for the manpower planning. The results of the workload analysis show that the workload limit control is from 107,96% to 126,62%. The workload for each job is as follows: Designer (107,11% - Underload), Mechanic (145,59% - Overload), System Developer (118,61% - Optimal), Quality Control Staff (98,46% - Underload). The manpower planning needed in the company are one designer, five mechanics, three system developers and one quality control staff. Keywords : manpower planning, work sampling, workload